Production of IGF-I and IGF binding proteins by retinal cells in vitro. Issue 8 (August 1994) - Moriarty, P; Boulton, M; Dickson, A; McLeod, D
Abstract : Insulin-like growth factor I (IGF-I) and its associated binding proteins (IGFBPs) have been identified in retinal tissues but their precise cellular origin remains unclear. The aim of this study was to examine the ability of three retinal cell types (microvascular endothelial cells, pericytes, and pigment epithelial cells) and a non-retinal cell type (Tenon's fibroblasts) to produce IGF-I and cell specific IGFBPs in vitro. Using a radioimmunoassay we demonstrated that all four cell types produce IGF-I and that this production continued over a 72 hour period. In addition, western ligand blotting revealed that each cell type produced at least one IGFBP and that each cell type produced a different IGFBP profile. Endothelial cells produced a 24 kDa band only, pericytes produced both a 24 kDa and a 34 kDa band, retinal pigment epithelial cells produced a 38-41 kDa band, while fibroblasts produced both a 24 kDa and a 30 kDa band. Laser scanning densitometry demonstrated that in the majority of experiments the IGFBPs accumulated in the culture medium over a 72 hour period. Neither IGF-I nor IGFBPs were observed in cell lysates indicating de novo synthesis and secretion in vitro. These results suggest an autocrine/paracrine function for IGF-I and its associated binding proteins which may play a significant role in both retinal physiology and disease.